Hypoxia-inducible factors in postnatal mouse molar dental pulp development: insights into expression patterns, localisation and metabolic pathways - Holomková, Kateřina; Veselá, Barbora; Dadáková, Kateřina; Sharpe, Paul T; Lesot, Hervé; Matalová, Eva; Švandová, Eva (Pflugers Archiv, 2024)
Hypoxia is relevant to several physiological and pathological processes and this also applies for the tooth. The adaptive response to lowering oxygen concentration is mediated by hypoxia-inducible factors (HIFs). Since HIFs were shown to participate in the promotion of angiogenesis, stem cell survival, odontoblast differentiation and dentin formation, they may play a beneficial role in the tooth reparative processes. Although some data were generated in vitro, little is known about the in vivo context of HIFs in tooth development. In order to contribute to this field, the mouse mandibular first molar was used as a model.The expression and in situ localisation of HIFs were examined at postnatal (P) days P0, P7, P14, using RT-PCR and immunostaining. The expression pattern of a broad spectrum of hypoxia-related genes was monitored by customised PCR Arrays. Metabolic aspects were evaluated by determination of the lactate level and mRNA expression of the mitochondrial marker Nd1.The results show constant high mRNA expression of Hif1a, increasing expression of Hif2a, and very low expression of Hif3a during early postnatal molar development. In the examined period the localisation of HIFs in the nuclei of odontoblasts and the subodontoblastic layer identified their presence during odontoblastic differentiation. Additionally, the lower lactate level and higher expression of mitochondrial Nd1 in advanced development points to decreasing glycolysis during differentiation. Postnatal nuclear localisation of HIFs indicates a hypoxic state in specific areas of dental pulp as oxygen demands depend on physiological events such as crown and root dentin mineralization.
Keywords: Odontoblasts; zubní dřeň; faktor 1 indukovatelný hypoxií - podjednotka alfa; Molar; vývojová regulace genové exprese; represorové proteiny; Hypoxia-Inducible Factor 1, alpha Subunit; Metabolic Networks and Pathways; Dental Pulp; Mice; In vivo; Repressor Proteins; moláry; transkripční faktory bHLH; Gene Expression Regulation, Developmental; odontoblasty; zvířata; Apoptosis Regulatory Proteins; Basic Helix-Loop-Helix Transcription Factors; Development; myši; proteiny regulující apoptózu; Dental pulp; metabolické sítě a dráhy; Hypoxia-inducible factors; Animals